2016
DOI: 10.1002/cbin.10579
|View full text |Cite
|
Sign up to set email alerts
|

E‐cadherin‐mediated contact of endothelial progenitor cells with mesenchymal stem cells through β‐catenin signaling

Abstract: Mesenchymal stem cells (MSCs) and endothelial progenitor cells (EPCs) are attached to each other in the bone marrow (BM) cavity and in in vitro cultures, and this adhesion has important physiological significance. We demonstrated that cell proliferation could be promoted when MSCs were co-cultured with EPCs, which was beneficial to angiogenesis, tissue repair, and regeneration. The adhesion of MSCs and EPCs could promote the pluripotency of MSCs, particularly self-renewal and multi-differentiation to osteoblas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…We have previously reported that MSCs and EPCs adhere to each other in the bone marrow cavity and in vitro ( 13 , 14 ), and that this mutual adhesion is important for the biological functions of both cell types. EPCs have also been reported to promote the differentiation of MSCs into osteoblasts ( 15 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously reported that MSCs and EPCs adhere to each other in the bone marrow cavity and in vitro ( 13 , 14 ), and that this mutual adhesion is important for the biological functions of both cell types. EPCs have also been reported to promote the differentiation of MSCs into osteoblasts ( 15 ).…”
Section: Resultsmentioning
confidence: 99%
“…BMMSCs were isolated using the technique reported in our previous studies ( 13 , 14 ). Briefly, bone marrow cells were collected from 6-week-old wild-type male C57BL/6 mice euthanized by cervical dislocation.…”
Section: Methodsmentioning
confidence: 99%
“…[ 94 ] The symbiotic relationship of the coculture has also been illustrated by the mutual attachment of MSCs and ECs (particularly EPCs), which augments the pluripotency of MSCs and simultaneously promotes angiogenesis. [ 95,161 ]…”
Section: Discussionmentioning
confidence: 99%
“…[94] The symbiotic relationship of the coculture has also been illustrated by the mutual attachment of MSCs and ECs (particularly EPCs), which augments the pluripotency of MSCs and simultaneously promotes angiogenesis. [95,161] Under optimal conditions, VEGF production by MSCs can be increased. The use of strontium-containing titanium material was reported to stimulate MSCs toward higher secretion of VEGF and platelet-derived growth factor-BB, which are both essential for angiogenesis.…”
Section: Angiogenic Response Of Ecs Mediated Through Other Cell Typesmentioning
confidence: 99%
“…This diversity depends on glycan composition and complexity of branching, which is cell type-specific [340,341]. Glycosylation regulates the biological activity of proteins, such as cell-cell and cell-extracellular matrix interactions, ligand binding affinity, protein trafficking as well as subcellular localization and protein stability [177,[342][343][344]. The IR, for example, is highly glycosylated in the ectodomains of the α and β subunit [345][346][347][348][349][350][351], which is essential for proper processing of the receptor [347,349,350].…”
Section: Protein Glycosylationmentioning
confidence: 99%